At war or saving lives? On the securitizing semantic repertoires of Covid-19. (June 2023) - Baele, Stephane J; Rousseau, Elise
This paper offers a multi-dimensional analysis of the ways and extent to which the US president and UK prime minister have securitized the Covid-19 pandemic in their public speeches. This assessment rests on, and illustrates the merits of, both an overdue theoretical consolidation of Securitization Theory's (ST) conceptualization of securitizing language, and a new methodological blueprint for the study of 'securitizing semantic repertoire'. Comparing and contrasting the two leaders' respective securitizing semantic repertoires adopted in the early months of the coronavirus outbreak shows that securitizing language, while very limited, has been more intense in the UK, whose repertoire was structured by a biopolitical imperative to 'save lives' in contrast to the US repertoire centred on the 'war' metaphor.